Age differences in emotional reactions to ageist memes and changes in age of one's Best Self - Kahlbaugh, Patricia; Ramos-Arvelo, Jacklyn; Brenning, Madison; Huffman, Loreen (Journal of Aging Studies, 2024)
Memes on social media can carry ageist messages and can elicit reactions that are both emotional and self-evaluative. The present study investigates age-related differences in nine discrete emotions and in the evaluation of when individuals have been or will be their best selves. Participants (n = 360) representing young (m = 26 years), middle-aged (m = 39 years) and older adults (m = 63 years) were randomly assigned to view either non-ageist (animals) or ageist (e.g., incompetent older people) memes. After viewing memes, we assessed nine emotional reactions (i.e., fear, anger, sadness, happiness, anxiety, discomfort, disgust, surprise, enjoyment) and Best Self evaluations. Younger and middle-aged people reported more intense emotional reactions to memes than older people, with the exception that older people reported more discomfort and disgust in response to ageist versus non-ageist memes. Younger adults were less surprised by ageist memes (vs. non-ageist) and for all age groups ageist memes (vs. non-ageist) elicited less happiness and enjoyment and were less likely to be shared. With respect to evaluations of one's Best Self, older individuals were more likely to report being their best selves in the past, while after viewing ageist memes, younger individuals were more likely to report being their best selves in the future. Emotions of disgust and discomfort were related to identifying one's Best Self as further in the past. The current study adds to the literature on the impact of ageism by examining age-related differences in the emotions and self-evaluations experienced when confronted with memes on social media.
Keywords: Ageism; Emotions; Self-evaluations; Social media/memes; dept.psy; peer-reviewed

Genome Sequences of Elezi, Asa16, and Niobe, Three Cluster AZ Phages Isolated Using Arthrobacter globiformis B-2979 - Elezi, Emanuela; Sellers, Erica; Abdulla, Alia; DeCiucis, Marisa A.; Lynch, Brielle R.; Nowak, Mark; Outlaw, Jamie; Ramos, Camila; Ramos-Arvelo, Jacklyn; Rokas, Sophia; Torres-Cintrón, Yadinitza; Uka, Simon; et al. (Microbiology Resource Announcements, 2022)
0 citations (Crossref) [2023-10-31]
Keywords: dept.bio